Reforming England's blasphemy law to protect the individual - Brown, Kevin Smullin (Islam and Christian-Muslim relations, 2003)
Using a framework of legal analysis proposed by Robert Post, this article examines the novel possibility of a reform in England's current criminal law of blasphemy. As previous attempts to include faiths other than Christianity faltered politically and theoretically, the article proposes a reform of the law to protect individual citizens and not religious groups. Different from incitement to racial or religious hatred legislation, this new offense would rest on what Joel Feinberg calls 'vicarious harm', the harm done directly to a person by deliberately wounding her sense of the sacred. The essay takes as given the propositions that equality before the law is desirable, a clear and ordered criminal offense is better than a vague criminal offense, and, as given specifically by the circumstances in England, a reverence for the transcendent sacred is privileged above other forms of reverence.